Mishaa,Farah. Aldaood ,Abdulrahman.Consolidation and collapse behavior of silty soil reinforced with plastic water bottles wastes - MishaaFarah- AldaoodAbdulrahman (University of Eloued جامعة الوادي, 2023)
This research paper has focused on the influence of plastic waste materials (water bottles) on the consolidation and collapse behavior of silty soil. The silty soil was randomly reinforced with various fiber content (0.5, 1.0 and 1.5% of the dry weight of soil) having various lengths of 10, 20 and 30 mm. The soil samples were prepared at the maximum dry unit weight and the optimum moisture content of unreinforced soil, (natural soil) using standard compaction efforts. The variation in the compaction, collapse and consolidation characteristics of unreinforced and reinforced soil samples were evaluated. The test results indicated that there was a slight reduction in both the maximum dry unit weight and the optimum moisture content of soil samples with fiber addition. The collapse index increased with increasing fiber content, while the fiber length enhance the collapsibility of silty soil. Further, the compression index of reinforced soil samples followed the same trend as the collapse index
Article
Keywords: silty soil; water bottles wastes; compaction; consolidation; collapse